Cultural and artistic education strategies: The institutionalisation aspect - Pavlova, Olena; Afonina, Olena; Vilchynska, Iryna; Khlystun, Olena; Smyrna, Lesia (Linguistics and Culture Review, 2021)
The relevance of this study is conditioned by the dual standards of institutionalisation of artistic and educational practices, must meet the principles of creating cultural objects as material products of high culture and aesthetic level, but, at the same time, must meet the requirements of the time, standards and educational tendencies of its time. Thus, a conflict of artistic vision and the standards of accumulated artistic experience is formed, which must be resolved in a process of dialogue and permanent collaboration of the two practices: educational and artistic. The purpose of this article is to investigate the basic vectors of the institutionalisation of educational and artistic practices, identifying priority ways of institutionalising both practices and the space for their interaction in scientific research. The main scientific methods for researching the topic are the basic general scientific theoretical methods of analysis, synthesis, induction, deduction, comparative to deduce the main regularities and characteristic features in the processes of institutionalisation of artistic practices, as well as systematisation and classification methods to form the structure of the main educational artistic strategies based on common and unique features.